A Path toward Safer Heritage Buildings through Excellent Fire Prevention and Control System in Malaysia - Othuman Mydin, Md Azree; Khaw, Yen Yen (Eftimie Murgu University of Resita, 2014)
Fire prevention & control system by Fire Rescue Department Malaysia states that protection in the aspects of fire prevention, control and extinguishment for a certain area based on the availability of risks in that area. It is a practice of mitigating the unwanted effects of fires. Besides that, a fire safety system also includes the study of the behaviour, compartmentalisation, suppression and investigation of fire and its related emergencies. In protecting and preserving the historic fabric of the heritage structure there are some major differences which is a challenge for the architect and fire protection engineer in the application of general fire protection principles. The challenge in protecting heritage structure is to maintain their historical fabric while providing a reasonable level of safety for their occupants and contents. In order to avoid harming the building’s historic character, the architect and engineer will need to have the sensitivity and ingenuity approaches to provide fire prevention and protection measures that do not damage the historic fabric of the building. This paper focuses on path toward safer heritage buildings through excellent fire prevention and control system in Malaysia.